9th International Conference on Rehabilitation Robotics, 2005. ICORR 2005. 2005
DOI: 10.1109/icorr.2005.1501156
|View full text |Cite
|
Sign up to set email alerts
|

Developments in locomotion interfaces

Abstract: This paper describes the Sarcos Treadport locomotion interface, a large tilting treadmill whose unique aspect is the application of forces to a user's torso. The application of torso forces is necessary to provide missing inertial forces during acceleration on a treadmill and to stop a user from walking through virtual walls. Torso forces can also substitute for treadmill tilt, as has been validated by psychological, biomechanical and energetic studies. A harness has been designed to transmit forces to the tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Hollerbach et al [5] reported a treadmill-based locomotion interface that used a mechanical tether to center users as they walked or ran on a larger treadmill. In addition to centering the user, the mechanical tether applied inertial forces to give the subject a natural feeling during acceleration and deceleration.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…Hollerbach et al [5] reported a treadmill-based locomotion interface that used a mechanical tether to center users as they walked or ran on a larger treadmill. In addition to centering the user, the mechanical tether applied inertial forces to give the subject a natural feeling during acceleration and deceleration.…”
Section: Related Workmentioning
confidence: 98%
“…Locomotion interfaces that attempt to simulate natural walking have been reported previously, but they were expensive for practical implementation (usually because they embodied features not needed for the experiments, such as rapid tilt for rough terrain simulation, split-belt walking, and support for running speeds) [5], were unstable without subject training [6], or did not actually simulate walking [7]. Hollerbach et al [5] reported a treadmill-based locomotion interface that used a mechanical tether to center users as they walked or ran on a larger treadmill.…”
Section: Related Workmentioning
confidence: 99%
“…These interfaces, despite the promising results, are not still in a commercial form, or in some cases (e.g., [6,8,19]) place demands that are impractical for many laboratories such as large space for the device and frequent, specialized maintenance with high costs.…”
Section: Introductionmentioning
confidence: 99%